Routledge philosophy guidebook to Rousseau and the social contract - Bertram, Christopher, 1958- (Routledge philosophy guidebooks., 2004)
Rousseau's Social Contract is a benchmark in political philosophy that has inspired and influenced moral and political thought since publication and is widely studied for this reason.